Appendicitis within an Amyand's hernia: a surprising finding. Issue 3 (12th March 2019) - Chiong, Corinna; Yoon, Peter; Boseto, Fred
Abstract: Amyand's hernia is a rare type of hernia where the appendix is found within the hernial sac. We present a case of appendicitis within an Amyand's hernia in a 72-year-old man who presented with a acutely painful, irreducible right inguinal lump. He underwent open appendicectomy and primary tissue repair with subsequent delayed elective mesh hernioplasty 3 months later.